A Randomised Trial of The Role of Medicine and Pharmacists on Christian Community - Didiek Hardiyanto Soegiantoro; Holy Rhema Soegiantoro; Gregory Hope Soegiantoro (Universitas Kristen Immanuel, 2022)
Introduction: Medicine has been an inseparable part of human civilization since there will always be a health problem in human life. In developing countries, certain religions and beliefs may distort the perception of medicine which lead to social problems that are faced by pharmacists and clinicians. Indonesia has a social background of animism and dynamism that it inherited from its ancestors and it made the community still believe in shaman healers and traditional or alternative medicine without scientific proof. Objective: This study measures community trust in medicine and pharmacists, especially Christian communities based on their spiritual beliefs and provides a descriptive description based on the measure. Variables involved include age, baptism status, and level of education. The benefit of this research for pharmacists is to provide pharmaceutical services based on community spiritual trust to create a comprehensive pharmaceutical care design, both scientifically and spiritually. Method: The research method used is cross-sectional. The measurement is done by a questionnaire with a Likert scale. The results of this study indicate that the role of medicine and pharmacists in the Christian community is influenced by age, baptism status, and education level. Result: High scores from the questionnaire results were obtained from the adult age group (17-60 years), high school education level, diploma and bachelor's degree, as well as the status of being baptized. Conclusion : the role of medicine and pharmacists in the Indonesian Christian community is more prevalent at a more mature age, higher educational level, and baptized status.